STRENGTHENING THE UNDERSTANDING OF INDIGENOUS LEADERS IN THE DEVELOPMENT OF HALAL TOURISM BASED ON RELIGIOUS MODERATION IN THE CALDERA OF LAKE TOBA - Maraimbang Maraimbang; Zulkarnain Zulkarnain; Mhd. Affandi Ketaren; Aidil Yasin Maruf (SOSIOEDUKASI, 2025)
This community service activity aims to strengthen the understanding of traditional leaders towards the concept of halal tourism based on the values of religious moderation in the Lake Toba Caldera area, especially in Dairi and Balige Regencies. The method used is Participatory Action Research (PAR), with stages of identification, planning, implementation, and reflection. The activity was carried out through workshops and intercultural dialogue forums involving traditional leaders, extension workers of the Ministry of Religion, tourism managers, and local communities as partners. The results of the activity show a positive change in the perception and attitude of traditional leaders towards the concept of halal tourism which was previously seen as exclusive to become an ethical and inclusive service. The implication of this activity is the formation of a collective awareness of the importance of religious moderation in the development of sustainable and harmonious tourism.